The General Arragement of Water Bus on Mahakam River's - Alamsyah, Alamsyah; Pawara, Muhammad Uswah; Ikhwani, Rodlian Jamal; Sitorus, Chris Jeremy Verian; Kumandang, Niti Gede (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2025)
Mahakam River has its own place in the hearts of domestic and foreign tourists. The beauty of the Mahakam river can be enjoyed by using a water bus made of wood. Currently, there are 2 (two) water buses available on the Mahakam river to serve tourists who want to explore its beauty. It was found that the water bus did not meet adequate safety and seaworthiness standards. Referring to the mission of the Tourism Office of the city of Samarinda, namely increasing the development of tourist destinations in the city of Samarinda, the renewal of tourist water buses that are adequate and in accordance with the standards of feasibility and safety is something that is really needed. The purpose of this study is to provide an alternative to the existing water bus design as an effort to rejuvenate the tourism fleet operating on the Mahakam river. The research stages include designing a general arragement for a tourism water bus that produces data in the form of main dimensions, hull form coefficients, lines plan, general arrangement, 3D design, and ship accommodation interiors. The results obtained are the main size of the ship with the following details; L = 14.04 m, B = 5 m, H = 1.4 m, T = 1.1 m, Vs = 10 knots, Engine Power = 87.4 HP (For 2 Engines), Number of Passengers and Crew = 80 Persons. Initial stability was found to meet the criteria.